2020
DOI: 10.22541/au.159060414.45388685
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

P wave duration in paroxysmal and persistent atrial fibrillation

Abstract: Functional and structural changes in atrial muscle constitute a substrate for atrial fibrillation. The pathological changes in the left atrium decrease conduction velocity and result in prolongation of the P wave duration. The aim of the study was to assess the duration of the P wave in patients with paroxysmal and persistent atrial fibrillation. The study group consisted of 119 patients diagnosed with atrial fibrillation, 57 women and 62 men, aged 65.3+/-9.4 years. There were 65 patients with paroxysmal AF an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…P-wave duration on surface 12-lead ECG has also been associated with AF recurrence after CA. 17,18 A long P-wave duration is associated with an enlarged LA 19 and atrial conduction disturbance. 20 We demonstrated that positive ALP was an independent predictor of AF recurrence after CA, and there were no significant differences in the LAD and P-wave duration on surface 12-lead ECG between the Recurrence and Non-Recurrence groups.…”
Section: P-saecg and Atrial Remodelingmentioning
confidence: 99%
“…P-wave duration on surface 12-lead ECG has also been associated with AF recurrence after CA. 17,18 A long P-wave duration is associated with an enlarged LA 19 and atrial conduction disturbance. 20 We demonstrated that positive ALP was an independent predictor of AF recurrence after CA, and there were no significant differences in the LAD and P-wave duration on surface 12-lead ECG between the Recurrence and Non-Recurrence groups.…”
Section: P-saecg and Atrial Remodelingmentioning
confidence: 99%
“…PWD on the surface 12-lead ECG has also been described to be associated with AF recurrence after CA. 18,19 A long PWD is reported to be associated with an enlarged LA 20 and atrial conduction disturbances. 21 We demonstrated that positive ALP was an independent predictor of AF recurrence after CA, and there were no significant differences found for the LAD and PWD on the surface 12-lead ECG between the recurrence and nonrecurrence groups.…”
Section: Prediction Of Af Recurrence After Ca Using P-saecgmentioning
confidence: 99%